2015
DOI: 10.4028/www.scientific.net/amr.1134.138
|View full text |Cite
|
Sign up to set email alerts
|

Bending Strength of Finger Jointed Kelat Wood (<i>Syzygium</i> spp.) as Affected by Finger Length and Orientation

Abstract: The aim of this study was to determine the bending strength of finger joint of Kelat wood (Syzygiumspp.) bonded using Phenol Resorcinol Formaldehyde (PRF). Three finger-jointed Kelat wood with finger length of 12 mm, 13 mm and 15 mm respectively were manufactured and tested. In addition, the effects of different orientation (horizontal and vertical) of fingers were also examined. Bending tests were carried out to determine the Modulus of Elasticity (MOE) and Modulus of Rupture (MOR) of the finger jointed sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The authors found that for all species, as the finger length increases, the bending strength also increases due to a larger bonding area [9]. In the study by Abdul Hamid et al [10], the impact of finger length and orientation on the bending strength of the finger joint made with Kelat wood (Syzygium spp. ), one of the commercial timbers in Malaysia, was determined.…”
Section: Introductionmentioning
confidence: 97%
“…The authors found that for all species, as the finger length increases, the bending strength also increases due to a larger bonding area [9]. In the study by Abdul Hamid et al [10], the impact of finger length and orientation on the bending strength of the finger joint made with Kelat wood (Syzygium spp. ), one of the commercial timbers in Malaysia, was determined.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, selecting the appropriate finger joint composition is of utmost importance, and considerable attention is dedicated to this aspect. [4] To enhance process efficiency and predictability, numerous authors [5][6][7][8][9] have investigated various aspects of finger joint strength using experimental research, mathematical modeling, and numerical simulation. Their research aims to achieve a single objective -improving process efficiency and control to enhance predictability.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review reveals only a handful of research papers related to structural finger joints produced using local Malaysian hardwood. Hamid et al (2016) managed to produce finger joints with more than 70% joint efficiency in bending (compared to unjointed wood) for kelat (Syzygium spp.) when using a 15 mm length finger profile.…”
Section: Introductionmentioning
confidence: 99%
“…Hamid et al. (2016) managed to produce finger joints with more than 70% joint efficiency in bending (compared to unjointed wood) for kelat ( Syzygium spp.) when using a 15 mm length finger profile.…”
Section: Introductionmentioning
confidence: 99%